THE USE OF SIGN LANGUAGE AS A MEDIA FOR DELIVERING INFORMATION ON NATIONAL TELEVISION NEWS BROADCASTS - Fitria, Tira Nur (Universitas Mahaputra Muhammad Yamin, 2024)
Sign language is communication using non-verbal words which are delivered without words but with body movements/body language or facial expressions. Sign language has evolved into a practical mode of communication that forms the basis of deaf communities. It is a visual-spatial language based on positional and visual elements including the shape of digits and hands, position, orientation, limb, and gestures. This signal can be seen in a small box at the corners of television newscasts. This research reviews the use of sign language as media in delivering information (news) in TV broadcasts. This research was library research. The analysis showed that news programs broadcast by television stations become one of the providers of information. The existence of sign language facilities in news programs at this time at least minimizes gaps in the right to access information among persons with deaf disabilities. Several previous studies show that sign language is media information read by the news anchor to the TV audience (viewers) with the intermediary of a sign language interpreter. Sign language plays an active role for deaf people based on three effects of mass communication which provide direct cognitive, affective, and conative effects for deaf people. There is a relationship between the influence of the use of sign language in news programs on deaf people such as attracting the attention of deaf audiences with an easy visualization. A presentation of the news is enough to meet the information needs of the deaf person by continuing to prioritize the latest information.